ECONOMIC CATEGORY VALUE IN THE CONTEXT OF DISCLOSURE OF INTEGRATED REPORTING IN ENTERPRISES MANAGEMENT SYSTEM - V.Yu. Makarenko (Економіка та право)
The question of interpretation of the definition value in the context of disclosure of the essence of the integrated reporting of domestic enterprises is considered. On the basis of analysis of various definitions of domestic scientists, provisions have been formed regarding the use of the economic category value as a value in determining the essence of integrated reporting of an enterprise. The need to resolve the issue of the lack of an officially approved translation of the International Standard on Integrated Reporting in Ukrainian has been emphasized. Changing the expectations of users of accounting information and the emergence of new requirements for its content gradually change the approaches to enterprise management. The article focuses on the lack of a unified approach to the definition of value in the context of determining the essence of integrated reporting and its content. The absence of an official version of the International Standard for Integrated Reporting in Ukrainian has been noted, which causes the problem of inconsistency in the correct application of the concept of value in the context of disclosing the essence of the process of forming integrated reporting by domestic enterprises. Summing up the practice of using the economic category value in the context of defining the essence of integrated reporting, a different understanding of the scope of this distinction is defined, which leads to terminological confusion. The necessity of settling an existing issue by the development and approval of the official translation of the International Standard on Integrated Reporting in Ukrainian has been argued. The article emphasizes the fact that the categories value and «to create value» should be considered through the prism of integrated thinking, that is, through the integrated links between the various operational and functional units of the organization and the capital that the organization uses or influences, focusing on on cost creation in the short, medium and longterm periods.